Implementasi Metode Permainan Kauny Quantum Memory Dalam Hafalan Al – Qur’an di SMP IT Hajjah Fauziah Binjai - Ramadani, Tania; Hemawati; Salim, Agus (LP2M STAI Darul Kamal NW Kembang Kerang NTB, 2024)
Memorizing the Qur'an is an activity that has many methods, including the talqin and talaqqi methods. However, both methods are often less interesting for students. Therefore, this study aims to implement the Kauny Quantum Memory Game Method as a fun alternative for students of SMP IT Hajjah Fauziah Binjai in memorizing the Qur'an. This method involves the use of illustrations and body movements related to the verses to be memorized, so that it is expected to increase interest and effectiveness in the memorization process. This study was conducted with a research and development approach using the Hanafin and Peck models. Data collection techniques used include observation, interviews, and distributing questionnaires to students and teachers. The results of this study indicate that the learning media with the Kauny Quantum Memory Game Method received a very good assessment from media experts and theory experts, with a high validation percentage of 96%. The implications of this study indicate that this method is not only effective in helping students memorize the Qur'an, especially the short letters in juz 30, but can also provide a more enjoyable and interesting learning atmosphere.